Prospective characterization of postoperative nasal deformities in patients undergoing endoscopic endonasal skull‐base surgery. Issue 2 (30th October 2019) - Rowan, Nicholas R.; Valappil, Benita; Chen, Jonlin; Wang, Eric W.; Gardner, Paul A.; Snyderman, Carl H.
Abstract : Background: Surgeons have become increasingly aware of the impact of endoscopic endonasal surgery (EES) of the skull base on sinonasal‐related quality of life. Prior retrospective investigation described a correlation between nasoseptal flap (NSF) reconstruction in EES with postoperative nasal deformities, such as nasal dorsum collapse. The primary objective of this study was to prospectively evaluate the incidence of, and contributing factors to, postoperative changes in nasal structure following EES. Secondary goals included assessing subjective changes in nasal appearance as well as objective nasal analysis. Methods: Clinical demographics and detailed perioperative information was prospectively collected for patients undergoing transsellar/suprasellar EES for skull‐base tumors. Preoperatively, 1‐month and 6‐month photographs were completed for objective photographic nasal analysis and blinded assessment by surgeons. Subjective patient feedback was also solicited. Results: Overall, 14.7% (5/34) of patients subjectively reported postoperative nasal deformities, whereas both blinded‐surgeon and objective nasal measurements identified deformities in 12.9% (4/31) of patients. Patients with postoperative deformities were more likely to have skull‐base reconstruction with an NSF ( p = 0.01) and trended toward an increased incidence in patients with nonpituitary neoplasms ( p = 0.07). There were no other associations between clinical or operative characteristics and external deformities. No patients planned to undergo corrective repair. Conclusion: External nasal deformities following EES are more frequent than previously acknowledged. Postoperative deformities appear to be associated with NSF reconstruction and may be associated with surgery for nonpituitary neoplasms. Patients should be counseled on this potential outcome, and future studies should investigate how to minimize postoperative sequela.